Relationship of hormonal profile and anxiety disorders in women — internally displaced persons with threatened miscarriage - I.Yu. Romanenko (Mìžnarodnij Endokrinologìčnij Žurnal, 2020)
Background. Pregnancy is an important, critical stage in the development of woman personality. Chronic stress can affect the course of pregnancy, leading to an increase in the number of complications. Displaced people usually have higher rates of depressive and post-traumatic symptoms than people from the host regions in which they relocate. In the antenatal period, the propensity to psycho-emotional disorders is increased, about 54 % of women experience anxiety during pregnancy. Threatened miscarriage is the most common complication of pregnancy that occurs in 15–20 % of cases of ongoing pregnancy and is associated with a complicated course of pregnancy and childbirth. Hormonal homeostasis plays an important role in the maintenance and development of pregnancy. The purpose of this research was to study the features of the relationship of the hormonal profile and anxiety disorders in women — internally displaced persons with threatened miscarriage, living in the Luhansk region, to improve treatment and preventive measures and prevent obstetric and perinatal complications in such women. Material and methods. The study included 24 pregnant women with the status of internally displaced persons, who were hospitalized for threatened miscarriage to the hospitals, located in the Luhansk region (group I). The control group (group II) consisted of 25 pregnant women with non-complicated obstetric anamnesis and physiological course of pregnancy with similar gestational period. The concentrations of estradiol, progesterone, cortisol and prolactin were determined. Spielberger State-Trait Anxiety Inventory was used to assess the level of anxiety. Results. Group I patients showed a statistically significant relative progesterone deficiency, a significant excess of stress-associated hormones such as prolactin and cortisol. Patients of group I had significantly higher levels of state and trait anxiety. A positive correlation was found between cortisol concentration and indicators of state anxiety in group I. According to multiple regression analysis, the predictors of anxiety disorders are the level of trait anxiety and the concentration of cortisol and progesterone. Conclusions. Antenatal study of indicators of anxiety, the level of stress-associated hormones, progesterone in pregnant women with threatened miscarriage will allow us to individualize the approach to the management of pregnancy and, if needed, to timely develop rehabilitation measures that will contribute to a successful outcome of the pregnancy and influence the health of the mother and her children.